Exploring How Motivation and Infrastructure Impact Learning Outcomes in Workshop and Technical Drawing Subjects for 10th Grade Students at SMK Negeri 5 Padang - Atikah Nur; Thamrin (Sagamedia Teknologi Nusantara, 2023)
This research aims to evaluate the contribution of motivation to students' learning outcomes, the contribution of infrastructure to learning outcomes, and the combined impact of motivation and infrastructure on the learning outcomes of 10th-grade students majoring in Audio-Video at SMK Negeri 5 Padang in the subjects of workshop and technical drawing. The research method employed is a descriptive method with a correlational approach. The study population includes all 10th-grade students majoring in audio-video at SMK Negeri 5 Padang registered in the Academic Year 2021/2022, comprising 2 classes with a total of 72 students. The sample for this study consists of 42 students. The results of the first, second, and third hypothesis analyses indicate that the null hypothesis (Ho) is accepted, while the alternative hypothesis (Ha) is rejected. These findings indicate that individual motivation and infrastructure do not significantly contribute to learning outcomes. Furthermore, the analysis of the third hypothesis indicates that students' perceptions of combined motivation and infrastructure also do not significantly contribute to learning outcomes. Specifically, learning motivation contributes 2.3%, while infrastructure contributes 0.26% to students' learning outcomes.